THE INFLUENCE OF FARMERS' INCOME ON CHILDREN'S EDUCATION LEVELS TO CONTINUE TO HIGHER COLLEGE IN RASAU JAYA TIGA VILLAGE - Retnowati, Putri Denzi; Sulistyarini, Sulistyarini; Anasi, Putri Tipa (GEOREFERENCE, 2024)
Rasau Jaya Tiga Village is a village that develops and is built on peatland areas. These peatlands are used as the main source of livelihood for the population. This village community depends entirely on agriculture to meet all needs, including primary needs (clothing, shelter, food), secondary such as access and facilities for children's education, and others. In Rasau Jaya Tiga Village, farmer children can still be found who do not continue their education to the tertiary level, this is due to the low participation rate in education. Education is one of the main foundations that with its presence brings hope that it will improve the dignity, dignity, and quality of human resources. The existence of this study was carried out with the aim and purpose of identifying the effect between farmers' income on children's education level to continue to university in Rasau Jaya Tiga Village, Rasau Jaya District. This study utilizes survey methods with a focus on the study of relationships or correlations with quantitative approaches. The sample in this study involved 85 farmers and data was obtained through questionnaires which were then analyzed. The results of the study show that there is an influence between farmers' income on children's education level to continue to university in Rasau Jaya Tiga Village. The results of data analysis using simple linear regression analysis testing produce a regression equation Y = 48.365 + 0.327X and indicate a constant value of 48.365. Meanwhile, it was found that the regression coefficient was positive at 0.327, illustrating that for every 1% increase in farmer income (variable X), the child's education level (variable Y) will increase by 32.7%.